Vita Sancti Servani and Vita Sancti Kentigerni : [Lives of St Sert and St Kentigern/ Mungo] / Jocelin of Furness. - Jocelin, active 1200
Towards the end of the twelfth century Bishop Jocelin of Glasgow commissioned Jocelin of Furness to write this Life of Kentigern. Its opening 12 pages are Jocelin of Furness' Life of St Serf, Kentigern's master.